Formative evaluation in Physical Education to school children with intellectual disabilities - Marilin Páez Basabe; Nordis Sánchez Quintero; Mercedes Miló Dubé (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2019)
This article presents the results of research aimed at the application of evaluation in Physical Education, in schoolchildren with intellectual disabilities, noting the poor correspondence between the objectives of the program being taught and the objectives proposed in the current evaluation model, through Ministerial Resolution 238/2014. The objective is to propose a formative evaluation methodology in Physical Education, for school children with intellectual disabilities, in the municipality of Pinar del Río. For this purpose, different research methods were applied, such as the observation of Physical Education classes at different times during the evaluation, and the survey of teachers of the subject who teach classes to schoolchildren. As a result, a methodology is presented which integrates the evaluation of motor skills and physical abilities and promotes recreational activities in which practical and social learning are stimulated, influencing the improvement of their health and preparation for an adult and independent life of schoolchildren.